Highly sensitive and flexible tactile sensor with truncated pyramid-shaped porous graphene/silicone rubber composites for human motion detection. (5th January 2022) - Wang, Yancheng; Chen, Zhijian; Mei, Deqing; Zhu, Lingfeng; Wang, Shihang; Fu, Xiang
Abstract: This paper presents a novel highly sensitive and flexible tactile sensor based on the fabrication of truncated pyramid-shaped porous graphene nanoplate (GNP)/silicone rubber (SR) composites as the sensing material. The designed tactile sensor has 3 × 3 (=9) sensing units, each unit has three layers: top cover layer with upper electrodes, middle truncated pyramid-shaped porous composite sensing materials, and substrate layer with bottom electrodes. The fabrication processes to make the truncated pyramid-shaped porous piezoresistive sensing material and tactile sensor were developed. The prepared porous GNP/SR composites possess extremely high sensitivities of 8.45 kPa −1  at 0–55 kPa and 195.02 kPa −1  at 55–80 kPa for pressure sensing, its Young's modulus is generally low (∼85.72 kPa), and can endure large strain over 60%. The sensing performances of the fabricated tactile sensor were also characterized, results show that the tactile sensor has high sensitivity, good dynamic response, and repeatability under cyclic pressure sensing. Human body wearing experiments were performed and results demonstrate that the developed tactile sensor was able to detect the distributed motion signals as well as human physiological signals such as pulse accurately, indicating that the proposed tactile sensor has great potential for human motion and health monitoring. Graphical abstract: Image 1 Highlights: A flexible tactile sensor with truncated pyramid composite structure is developed. A foaming method to fabricate porous composite sensing material is proposed. The tactile sensor exhibits an extremely high sensitivity and flexibility.